Diseño e implementación de un MRaaS, manipulador robótico tipo Scara como servicio en la nube. - Pilatasig Chanatasig, Edison Mauricio (2015)
Today there are many designs and applications involving communication, control and computing. These applications generate network control systems, which are systems composed of a lot of integrated entities, sensor nodes coupled through a common communication network for manipulation and physical control processes, as well as robotic devices, network control systems are generating applications that are becoming ubiquitous and useful in several areas such as health care, disaster management, flexible manufacturing, education, etc., but network control systems implementation still faces several challenges such as cost and efficiency of resources. This work focuses on the implementation of a cloud service for remote control of a robotic manipulator, that develops an infrastructure (IaaS) for the robotic arm, a service is programmed in C # (PaaS) that gives access to remote users (SaaS) to create a MRaaS unit. A relational data base with tables and fields needed is created to cover with: user management, station management, permissions and hierarchies for using the platform, session management, connection and records, modular systems are used on the side of the workstation and also capabilities to support various robotic actuators in order to be manipulated simultaneously, and the use of Kinect sensor for detecting the desired movements.